THE INFLUENCE OF PRICE, BRAND IMAGE, AND LIFESTYLE ON PURCHASING DECISIONS OF BRANDED SECONDHAND CLOTHING (THRIFTING) IN SAMARINDA CITY - Hilmi Akbar; Annisa Wahyuni Arsyad; Lailatul Hijrah; Ummi Nadroh (Faculty of Social and Political Sciences, Universitas Lampung, 2025)
This study aims to examine the influence of price, brand image, and lifestyle on purchasing decisions of branded secondhand clothing (thrifting) in Samarinda City. The background of this research is based on the growing interest in thrifting as an alternative fashion choice that is affordable, unique, and environmentally friendly. This study adopts a quantitative approach with purposive sampling. The sample consisted of 108 respondents who have purchased branded secondhand clothing from several popular thrift stores in Samarinda. Data were collected through questionnaires and semi-structured interviews. The data analysis was conducted using SPSS version 24, involving validity and reliability tests, multiple linear regression analysis, t-test, F-test, and coefficient of determination. The results show that partially, price and brand image do not have a significant effect on purchasing decisions. However, lifestyle has a significant effect on purchasing decisions. Simultaneously, price, brand image, and lifestyle have a significant influence on consumers' decisions to purchase branded secondhand clothing in Samarinda. These findings indicate that consumers' lifestyle—particularly in terms of fashion preferences and the desire for uniqueness—plays a dominant role in influencing purchasing decisions in the context of thrifting.